Childhood Narcissism: Strategies to Raise Unselfish, Unentitled, and Empathetic Children - Little, PhD, Mary Ann (Rowman & Littlefield Publishers, 2023)
"Not a quick how-to, this is for the parent, clinician, or caregiver seeking in-depth information and guidance.” - Booklist Notice the signs of narcissism in your child and act to curb them before it’s too late Raising empathetic and unselfish young people in today’s “all about me” world might seem impossible, but parents can take meaningful action to protect children from these harmful influences. Written by a psychologist with decades of clinical experience, Childhood Narcissism explains how selfish, entitled behavior can take root in a child and shows parents how to stop it before it’s too late. Mary Ann Little identifies the early warning signs that can result in a full-blown narcissistic disorder in adulthood and explores what nurtures a child’s healthy, realistic self-concept and provides a positive model of love and relationships. Based on the latest research and theory, Childhood Narcissism also identifies four parent types that promote narcissistic development. By recognizing these traits in themselves, parents can work on their own shortcomings to build a stronger family and raise caring, empathetic children.